Coral fish diversity in Netrani waters off Murudeshwar Karnataka, south India - Thomas, Sujitha; Sreeram, Miriam Paul; Kakati, V. S.; Manisseri, Mary K; George, Rani Mary (Indian Journal of Fisheries, 2011)
Fish diversity associated with coral reef patches around Netrani Island, in Karnataka (south India) was investigated by visualcensus method. Sampling was done in four sites around the Island. A total of 69 species belonging to 39 genera, 19 familiesand 3 orders were recorded in the transect in four sites. When comparing the abundance, the fishes of Balistidae familydominated in all the four sites (22 %) followed by Pomacentridae (12.5 %), Caesionidae (9.7 %), Labridae (7.8 %), Acanthuridae(7.3 %), Haemulidae (6.7 %) and Scaridae (6.1 %). In line with the abundance and number, Shannon diversity indices (H’)were 2.8 in site 1; 2.6 in site 3; 2.3 in site 4 and 2.2 in site 1. The evenness (J’) of species distribution was more in site 2 (0.9),followed by site 3 (0.8); site 4 (0.7) and site 1 (0.7). The Bray-Curtis similarity was in the range of 69.98 to 79.50.The dendrogram plotted showed that site 2 and 3 form a group with similarity of 79.50, to which site 1 and site 4 got linked.There was no significant difference in the hydrographic parameters of the surface and bottom waters in four sites and alsobetween different sites. The study revealed high coral fish density in the area indicating the need for adopting conservationmeasures.